Perception of HIV among pregnant women in the public health system in two municipalities of the state of São Paulo - Garbin, Cléa Adas Saliba [UNESP]; Pacheco, Karina Tonini dos Santos; Santiago, Thaís Fonseca; Miyada, Simone [UNESP]; Garbin, Artênio José Ísper [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (FapUNIFESP (SciELO), 2015)
Aim: To verify the knowledge of pregnant women on mother-to-child transmission (MTCT) of HIV, the availability of HIV tests in the public health system and counseling on the disease in two cities, Birigui and Piacatu, São Paulo State, Brazil. Methods: This is a descriptive and exploratory research using as samples, the files of 141 pregnant women attending the Basic Health Unit. Data were collected by survey, followed by a semi-structured questionnaire with open and closedend questions. Data were analyzed on Epi InfoTM 7.1.4, by the Chi-square and Exact Fisher tests. Results: From all the 141 pregnant women, 119 were interviewed and 92.4% reported to have been informed about the need of taking the HIV test during prenatal exams. However, only 5.9% were counseled and 20.2% reported to be aware of how to prevent MTCT of HIV, usually mentioning lactation suppression and prescribed medication. The association between the knowledge about how to prevent MTCT of HIV and some social, demographic and economic variables like ethnics, educational level, home location, occupation, age and parenting was not verified. Conclusions: It is necessary to advise pregnant women on the importance of taking the HIV test regardless of the examination outcome, which was not observed in the cities where the research was conducted.
Keywords: HIV; Maternal and child health; Public health